The Impact of Omega 3 Fatty Acids in Atherosclerosis and Arterial Stiffness: An Overview of their Actions - Verveniotis, Alexios; Siasos, Gerasimos; Oikonomou, Evangelos; Tsigkou, Vasiliki; Papageorgiou, Nikolaos; Zaromitidou, Marina; Psaltopoulou, Theodora; Marinos, Georgios; Deftereos, Spyridon; Vavuranakis, Manolis; Stefanadis, Christodoulos; Papavassiliou, Athanasios G.; et al. (Current Pharmaceutical Design, 2018)
Background: Fatty acids are common dietary nutrients particularly in economically developed countries. Research has revealed that omega-3fatty acids exert beneficial effects in the progression of atherosclerosis and cardiovascular disease. Moreover, eicosapentaenoic acid and docosahexaenoic acid possess a number of biological actions which improve cardio-metabolic health. Omega-3 fatty acids display remarkable anti-oxidant, anti-inflammatory, anti-thrombotic and anti-arrhythmogenic actions. Furthermore, they improve the levels of triglycerides, glucose metabolism and endothelial function. Methods: The aim of this review article is to present physical, biochemical and biological properties of omega-3 fatty acids and summarize the most important mechanisms of action on arterial wall properties and arterial stiffness in atherosclerosis. Results: Omega-3 fatty acids may prevent the progression of atherosclerosis. Endothelial dysfunction and arterial stiffness can be regulated by the supplementation of omega-3 fatty acids. Conclusion: The mechanisms of action of omega-3 fatty acids on cardiovascular health and arterial stiffening have been established. However, further research is needed in order to translate the conflicting results among the studies and improve the therapeutic options of cardiovascular disease.
Keywords: oxidative stress